Pelatihan Dan Pendampingan Pembuatan Media Pembelajaran Bagi Anak Berkebutuhan Khusus Di SLB Di Jawa Timur (Eduscotech, 2023)
The acceleration of technological development requires special education institutions to transform in order to provide adaptive and inclusive educational services. This community service program aimed to enhance the competencies of special school (SLB) teachers in East Java in designing learning media based on instructional technology and graphic design. The program employed intensive training and mentoring methods, resulting in the development of a digital learning platform that serves as a repository for teachers’ creative works and as a medium for accessing character education and skill-based learning materials for students with special needs. The primary focus of the program was to establish a digital ecosystem that supports independent learning at home with parental assistance, thereby strengthening collaboration between schools and families in fostering holistic student development. The results indicated a significant improvement in teachers’ confidence and professional capacity in responding to dynamic curriculum demands. Institutionally, the implementation of the digital platform enhanced the schools’ image as innovative educational institutions committed to inclusive media development. The program also demonstrated tangible impacts, including the provision of educational services that are no longer constrained by time and space, as well as increased institutional attractiveness to government and private sector support. This program concludes that mastery of instructional technology is a critical factor in building a competitive and sustainable special education ecosystem aligned with current labor market demands.